Dentinal tubules occluded by bioactive glass-containing toothpaste exhibit high resistance toward acidic soft drink challenge - Bakri, Marina Mohd; Hossain, Mohammad Zakir; Razak, Fathilah Abdul; Saqina, Z.H.; Misroni, A.A.; Ab-Murat, Norintan; Kitagawa, J.; Saub, Roslan (Wiley, 2017)
Background: Dentine hypersensitivity is a common problem attributed by patent dentinal tubules. Ingredients incorporated in toothpastes aim to occlude patent dentinal tubules to minimize the dentine hypersensitivity. However, frequent consumption of acidic soft drinks may reverse the dentinal tubules' occlusion. In this in vitro study, the efficacy of dentinal tubules occluded by commercially available toothpastes to withstand different durations of an acidic soft drink challenge was investigated. Methods: One hundred and twenty dentine discs were divided into three groups. The discs from each group were brushed with toothpaste containing bioactive glass, arginine and control toothpaste. Each group was then divided into four subgroups and exposed to acidic soft drink over four different time durations. Results: The scoring and the percentage of occluded dentinal tubules by Novamin-containing toothpaste was significantly better compared with arginine or the control toothpaste. Acidic soft drink challenge reduced the extent of dentinal tubules occlusion along with time. Dentinal tubules occluded by Novamin-containing toothpaste withstand the acidic challenge comparatively for a longer period. Conclusions: The findings demonstrated that occlusion of dentinal tubules is more efficient by the bioactive glass-containing toothpaste and thus may contribute to its better resistance to acidic soft drink challenge.